68Ga-PSMA-11 positron emission tomography detects residual prostate cancer after prostatectomy in a multicenter retrospective study - Farolfi, Andrea; Gafita, Andrei; Calais, Jeremie; Eiber, Matthias; Afshar-Oromieh, Ali; Spohn, Fabian; Barbato, Francesco; Weber, Manuel; Ilhan, Harun; Cervati, Veronica; Wetter, Axel; Hadaschik, Boris; et al. (The journal of urology, 2019)
Purpose: - Prostate specific antigen persistence after radical prostatectomy is associated with adverse outcomes in patients with prostate cancer. We sought to define regions at risk for residual disease as well as the accuracy of prostate specific membrane antigen ligand positron emission tomography in patients with prostate specific antigen persistence. Materials and Methods: - At 6 participating centers a total of 191 patients who underwent 68Ga-prostate specific membrane antigen-11 positron emission tomography/computerized tomography or positron emission tomography/magnetic resonance imaging for persistently elevated postoperative prostate specific antigen (0.1 ng/ml or greater) were retrospectively included in study. The detection rate and the positive predictive value were determined. In 33 patients with additional prostate specific membrane antigen ligand positron emission tomography before prostatectomy we also determined the rate of positron emission tomography based persistence and recurrence. Results: - Prostate specific membrane antigen ligand positron emission tomography localized prostate cancer in 130 of 191 patients (68%) with prostate specific antigen persistence at a median prostate specific antigen of 1.1 ng/ml. The detection rate significantly increased with prostate specific antigen (p <0.001). Regarding prostate specific membrane antigen positron emission tomography/computerized tomography only 61 of 173 patients (35%) had disease confined to the pelvis while 57 of 173 (33%) had distant lesions. The most frequently affected nodal regions were the obturator in 42% and the presacral/mesorectal region in 40%. In 15 of the 33 patients (45%) with prostate specific membrane antigen ligand positron emission tomography before and after surgery at least 1 lesion was detected at baseline (positron emission tomography persistence), 8 (24%) had new lesions (positron emission tomography recurrence) and 10 (30%) had negative positron emission tomography findings. The positive predictive value of prostate specific membrane antigen ligand positron emission tomography was 91%. Systemic therapy initiation was significantly associated with distant lesions on prostate specific membrane antigen ligand positron emission tomography. Conclusions: - Prostate specific membrane antigen ligand positron emission tomography localized prostate cancer in more than two-thirds of patients with high risk features and prostate specific antigen persistence after prostatectomy. Obturator and presacral/mesorectal nodes are at high risk for persistent metastasis.